Applications of Chitin in Medical, Environmental, and Agricultural Industries - Uday Dave; Esther Somanader; Parnian Baharlouei; Linh Pham; M. Azizur Rahman (Journal of Marine Science and Engineering, 2021)
Chitin is a universal biopolymer that is found in microbes, plants, fungi, the exoskeleton of insects, various species of algae, and bottom-feeding crustaceans. This (1–4)-linked N-acetyl-ß-D-glucosamine polysaccharide can be readily processed with simple chemical procedures without putting a species at risk. Chitin has garnered interest as an alternative substance that can be used in the medical, environmental, and agricultural sectors. Indeed, chitin’s unique nature of biocompatibility, being environmentally safe, and having innate water-solubility allows the polymer to be used in a wide range of applications. In this review, we discuss the possible applications of chitin in the medical, environmental, and agricultural sectors through an extensive search of the latest literature. Moreover, the following review summarizes and explores the new and current studies surrounding the practical uses of chitin to solve issues that are commonly induced by various chemicals which are invasive to the surrounding environment and species co-existing in that area.